2020
DOI: 10.3390/ijerph17228688
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity, Loneliness, and Social Isolation. A Systematic Review

Abstract: No systematic review has appeared so far synthesizing the evidence regarding multimorbidity and loneliness, social isolation, or social frailty. Consequently, our aim was to fill this gap. Three electronic databases (PubMed, PsycINFO, and CINAHL) were searched in our study. Observational studies examining the link between multimorbidity and loneliness, social isolation, and social frailty were included, whereas disease-specific samples were excluded. Data extraction included methods, characteristics of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 44 publications
4
45
1
4
Order By: Relevance
“…Among them, social support seems to have an effect on health [ 42 ]. In fact, the lack of relationships or social bonds was associated with physical or mental disorders [ 43 , 44 , 45 , 46 , 47 ]. Furthermore, social isolation, especially among the elderly, leads to lower health care utilisation, which produces poorer health status [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, social support seems to have an effect on health [ 42 ]. In fact, the lack of relationships or social bonds was associated with physical or mental disorders [ 43 , 44 , 45 , 46 , 47 ]. Furthermore, social isolation, especially among the elderly, leads to lower health care utilisation, which produces poorer health status [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growing concerns pertaining to increases in loneliness in the community prior to COVID-19 are related to the fact that loneliness is known to be associated with increased mortality and reduced quality of life (Groarke et al, 2020;Hajek et al, 2020). Research has indicated that loneliness contributes to both physical and mental health conditions as well as being associated with decreases in cognitive functioning (Groarke et al, 2020;Hajek et al, 2020;Jeste et al, 2020). Furthermore, the impact of loneliness on an individual's health has been equated with the impact of other factors that are well known to be detrimental to health, such as smoking, obesity and a lack of physical activity (Fakoya et al, 2020).…”
mentioning
confidence: 99%
“…Os indivíduos estão cada vez mais conectados digitalmente, mas a prevalência da solidão também parece estar aumentando. É muito comum encontrarmos nos meios de comunicação a temática da solidão [20][21][22][23][24] .…”
Section: A Solidão Na Contemporaneidadeunclassified